Kinerja Keuangan dan Manajemen Wakaf Sabilillah Malang - Wahyu Kharismaputri; Ulfi Kartika Oktaviana (UPT Penerbitan Universitas Jember, 2020)
Improving performance is critical in every organization including waqf institutions. Assessing performance can be useful to indicate whether they have been effective and efficient in managing waqf assets. In the context of non-profit organizations such as waqf institutions that aim to prosper the community still do not realize the importance of assessing performance. Waqf management is indispensable for the usefulness of waqf assets. Waqf will provide benefits for ummah if managed professionally. Nadzir is obliged to manage and develop waqf property in accordance with its purpose, function, and provision. This research uses qualitative methods with a deksriptif approach, which aims to know the financial performance and management of waqf in Sabilillah Mosque Malang. Data collection is done by means of interviews, observations, and library studies. The results showed that financial performance is quite good because it meets the criteria of the seven financial ratios. Waqf management in Sabilillah is also well organized according to their respective jobdisks. In waqf management in Sabilillah mosque use the principles of al-amin (siddiq, amanah, tabliq, and fathanah). nature of waqf property management has obstacles such as nadzir who are still passive in overseeing the management of waqf, but everything is implemented to the maximum extent possible and planned to give the same understanding to the waqf manager at Sabilillah mosque.